ANALYSIS OF THE DIFFICULTY OF STUDENTS 'MATHEMATICS LEARNING IN CLASS VIII FUNCTION MATERIALS - Tri Yuniatun; Fariz Setyawan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
State Junior High School (SMP Negeri) 1 Tempel students in mathematics are still low. Judging from the mathematics scores of Year-End Assessment (PAT) class VIII SMP Negeri 1 Tempel show that as many as 98.40% of students have not reached the minimum completeness criteria (MCC). Based on interviews with students, it was found that learning mathematics was complicated. Students tried to solve math problems but had difficulty solving them. Therefore, the purpose of this study is to determine the problems experienced by students in solving math problems and the factors that cause real challenges, conceptual difficulties, and procedural difficulties in learning mathematics in the function material of class VIII SMP Negeri 1 Tempel in the 2019/2020 school year. This research method is qualitative research. The subjects of this study were 31 students of class VIII A SMP Negeri 1 Tempel. The object of this research is learning difficulties in factual, conceptual, and procedural aspects. Retrieval of data using tests and interviews. The test instrument is in the form of function material questions. Data analysis techniques used the Miles and Huberman model, namely Data Reduction, Data Display, and Data Verification. The results of this study indicate that students have difficulty learning mathematics in terms of functions. Students' problems in the function material obtained 69.25% real difficulties, 63.79% conceptual difficulties, and 61.41% procedural difficulties. Students have a problem in (1) the factual aspect, namely writing the name of the function, writing the set's name, making arrow diagrams, making Cartesian diagrams, and writing the set of consecutive pairs. (2) Students have difficulty defining a function in the conceptual aspect, giving reasons why a relationship can be called a process, distinguishing the origin from the relationship, describing the origin and result area, calculating the number of members of the set, and writing the formulas a function. (3) procedural aspects, students are still lacking in determining the correct and appropriate steps in solving problems. Some students have difficulty determining what steps to take first. Thus resulting in incomplete procedures in solving questions. The factor that causes difficulty in learning mathematics in the function material is students' inaccurate learning patterns. This causes students to forget often and be confused when solving questions.